Production of hydrogen via hydrolysis using aluminum waste can powder composites for carbon dioxide methanation - Lim, Seng Tat (2022)

(untitled)
Hydrogen (H2) is a promising solution to conventional fossil fuel energy because it gives near-zero carbon emission and contains high calorific value. Recently methanation of carbon dioxide (CO2) using H2 is gaining interest. Many studies have focused on catalyst optimization of the methanation process. However, no studies have been performed to study methanation using clean H2. The common methanation process uses commercial H2 gas, which is more expensive and therefore not commercially feasible. Therefore, a clean and sustainable H2 production method is needed for methanation. Aluminium waste can powder (AWCP) which was synthesized by novel disintegration method was used in hydrolysis reaction to produce H2 gas. Different types of alkaline solutions, different types of water sources, and different durations of disintegration time were investigated to study their effects on hydrolysis. AWCP and selected pure metals (i.e., Zinc (Zn), Tin (Sn), Magnesium (Mg) and Indium (In)) were mechanochemically activated by the ball milling method to synthesize binary AWPC composites (i.e., AWCP/Zn, AWCP/Sn, AWCP/Mg and AWCP/In) and ternary AWCP composites (i.e, AWCP/Sn/Mg and v AWCP/Sn/In) to maximize H2 production by forming microgalvanic cells. Branauer-Emmet-Teller (BET) analysis proved that disintegration method using medicine blender is novel as Field Emission Scanning Electron Microscopy (FESEM) confirmed uneven fresh surfaces that are flaky in structure compared to pore-like structure of commercial Al. This method increased the BET surface area of the AWCP composites and contributed to a higher H2 yield due to ball-to-ball and ball-to-jar collisions during the ball milling process, which helped water to penetrate Al more effectively. The addition of pure metals to AWCP could reduce the total reaction time significantly. Binary AWCP (3% Sn), produced 1360 ml/g H2 in 240 s. However, ternary AWCP (3% Sn-3% Mg) produced 1320 ml / g of H2 in 660 s. XRD analysis confirmed the formation of intermetallic phases in AWCP (3%Sn – 3% Mg). Upon optimizing the H2 production, the gas was tested to produce methane (CH4) using CO2 in a catalytic system. In batch methanation, AWCP (3% Sn-3% Mg) generated much higher CH4 because it had a longer total reaction time and allowed longer residence time for H2 and CO2 to react. The pure AWCP (100%) produced the highest CH4 production due to low gas hourly space velocity (GHSV). For continuous methanation, AWCP (3% Sn) yielded the highest amount of CH4 despite high GHSV because a lot of unreacted H2 was left for further reaction continuously. In this study, a feasible and sustainable clean generation of H2 for use in methanation was successfully achieved.